SDG 6 progress analyses in sub-Saharan Africa from 2015–2020: the need for urgent action - Megersa Olumana Dinka; Joan Nyika (Discover Water, 2024)
Abstract This study used data from various international databases to track the progress of SDG 6 target indicators in sub-Saharan Africa (SSA) region between 2015 and 2020. Findings showed that although minimal positive progress was realized in the evaluation period, more than half of SSA residents had no access to safe drinking water services, improved sanitation facilities, hygiene services and safe wastewater treatment. The computed SDG 6 profile index conformed with the trend of indicators as progress of the region to the goal’s realization was rated as medium–low. The trend was further compounded by limited data, preferential access to water and sanitation services to the urban rich and poor monitoring of progress. The analysis also noted that despite these challenges the region was putting concerted efforts to promote transboundary cooperation in water management and had 6% of water stressed resources. The study recommended on the need to revamp water data collection and monitoring efforts to enable decision-making and planning on management actions, use of technology to treat and reuse wastewater as well as device new sources of water, enhanced participation of communities in water projects and improved water use efficiency to steer progress towards SDG 6 realization in SSA region.